Trends of virtual reality for learning empirical evidence from different fields - Siti Drivoka Sulistyaningrum; Rizky Syahra Putri; Atika Herawati; Sugeng Irianto (Journal of Education and Learning (EduLearn), 2022)
Virtual reality (VR) has been shown to be beneficial for educational purposes and has emerged as a prevalent topic for teaching and learning. However, there is very little that is currently known about VR in the context of learning from different fields. This research is a systematic literature review which intends to investigate the future trends of virtual reality for learning by analyzing real-world data obtained from Google Scholar, Crossref, and Google Trends; the first pertinent publication discovered in the database is included as the data of this study. In total, 451 relevant publications from Google Scholar and 999 relevant publications from Crossref have been identified by utilizing content analysis. Based on the findings, VR is an immensely new and emerging worldwide topic that involves authors and connections from various countries. Overall, the significant increase in publications on “virtual reality for learning” (as a source of knowledge) in recent years corresponds to the growing trend of Internet searches on “virtual reality for learning” (as a practical demand). These findings contribute to a reference, to promote, to adjust and re-align VR in workplace learning. This study only covers publication trends, including the number of publications per year and the source types of publications, as well as internet search trends from 2004 to 2022.